2011
DOI: 10.1088/0004-6256/142/5/158
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Emission From Young Stars in the Massive Star-Forming Region Iras 20126+4104

Abstract: We present a 40 ks Chandra observation of the IRAS 20126+4104 core region. In the inner 6 two X-ray sources were detected, which are coincident with the radio jet source I20S and the variable radio source I20Var. No X-ray emission was detected from the nearby massive protostar I20N. The spectra of both detected sources are hard and highly absorbed, with no emission below 3 keV. For I20S, the measured 0.5-8 keV count rate was 4.3 counts ks −1 . The X-ray spectrum was fitted with an absorbed 1T APEC model with a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…W51 IRS2E is exceptional even compared to the other very young, embedded massive stars with hard X-ray emission that we have described in the MOXC sample; in order for its emission to be concentrated in this reprocessed fluorescent neutral Fe line, the ionizing source itself must be producing most of its high-energy photons above the Fe absorption edge at 7.1 keV. A similar source is found in the MSFR IRAS 20126+4104 (Anderson et al 2011). Figure 11(e) shows a bright X-ray source with a K < 10 2MASS counterpart, likely the mid-O-type massive star ionizing radio H ii region "g" (Mehringer 1994), called source #4168 in "Region 2" defined by Okumura et al (2000).…”
Section: W51amentioning
confidence: 53%
“…W51 IRS2E is exceptional even compared to the other very young, embedded massive stars with hard X-ray emission that we have described in the MOXC sample; in order for its emission to be concentrated in this reprocessed fluorescent neutral Fe line, the ionizing source itself must be producing most of its high-energy photons above the Fe absorption edge at 7.1 keV. A similar source is found in the MSFR IRAS 20126+4104 (Anderson et al 2011). Figure 11(e) shows a bright X-ray source with a K < 10 2MASS counterpart, likely the mid-O-type massive star ionizing radio H ii region "g" (Mehringer 1994), called source #4168 in "Region 2" defined by Okumura et al (2000).…”
Section: W51amentioning
confidence: 53%
“…43 (CXO J201426.2+411327.9, 33 counts). The latter two sources correspond to the radio sources I20S and I20var (Hofner et al 2007), respectively, and have recently been discussed by Anderson et al (2011).…”
Section: Vla 6 CM Continuummentioning
confidence: 90%
“…Results for the two massive protostellar candidate sources I20S and I20var have recently been reported by Anderson et al (2011). We refer to this paper for a more detailed description of the observations and basic data reduction.…”
Section: Chandra Acis-imentioning
confidence: 97%
See 1 more Smart Citation
“…However, the high median energies of the counts (≈3-6 keV) and the elevated hardness ratios 3 (≈0.5-1.0) of the targets suggest that the spectra are quite hard. Previous X-ray studies of young H ii regions have also found that hard X-rays dominate their emission (e.g., Tsujimoto et al 2006;Anderson et al 2011), which may indicate very hot plasma temperatures (with kT X 6 keV) and/or extreme column densities (of N H 10 23 cm −2 ) that attenuate the soft X-rays.…”
Section: Hot Gas Pressurementioning
confidence: 94%